2002
DOI: 10.1021/ma010354q
|View full text |Cite
|
Sign up to set email alerts
|

Structural Molecular Dynamics Studies on Polyamidoamine Dendrimers for a Therapeutic Application:  Effects of pH and Generation

Abstract: Extensive simulations of PAMAM dendrimer generation 2 were performed at several pH conditions with explicit water molecules, to obtain proper conditions and validity for additional simulations without explicit water. Within the range of validity, simulation without water greatly extends the size and duration of practical simulations. We investigated the effects of long-range interaction parameters such as interaction distance and dielectric constant for molecular dynamics simulations of PAMAM dendrimer without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
267
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(293 citation statements)
references
References 30 publications
(46 reference statements)
21
267
3
2
Order By: Relevance
“…This is consistent with previous findings that the radius of gyration of PAMAM increases (swollen) at low pH. 8,29 The time evolution of normalized C d (t) for water in the neutral, unprotonated PAMAM solutions is depicted in Figure 3, parts a and b, and those of surface water and buried water around PAMAM at different protonation levels are compared in Figure 3, parts c-f. The water relaxation is determined by …”
Section: Definition Of Water Regimessupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous findings that the radius of gyration of PAMAM increases (swollen) at low pH. 8,29 The time evolution of normalized C d (t) for water in the neutral, unprotonated PAMAM solutions is depicted in Figure 3, parts a and b, and those of surface water and buried water around PAMAM at different protonation levels are compared in Figure 3, parts c-f. The water relaxation is determined by …”
Section: Definition Of Water Regimessupporting
confidence: 89%
“…At low pH (∼5), all the 128 primary amines and 126 tertiary amines are protonated. 29 For protonated PAMAM dendrimers, the protons are added before immersing them into water. Short minimization was performed to relax the added proton and its neighboring atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…13,31 Due to the increased availability of space in the dendrimer's interior, water molecules can penetrate even at distances near the center of mass, assuming an almost constant profile characterized by a value close to the density of bulk water.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] A particular class of such moleculessnamely, poly(amidoamine) dendrimers (PAMAM)shas been widely considered for biomedical applications. Properties such as biocompatibility, 10 water solubility, versatility in modifying their functional groups, 11 and responsiveness of their conformational properties to an aqueous environment 12,13 render these molecules appropriate for such uses. These attributes enable PAMAM dendrimers to enhance drug solubilization and to facilitate the transport and the controlled release of complexed pharmaceutical and biological molecules at targeted sites.…”
Section: Introductionmentioning
confidence: 99%
“…42 It has been shown that at pH values between 7 and 8, only dendrimer primary amines are protonated. 43,44 Therefore, we used this convention in modeling the dendrimers at neutral pH used in the experiment. The dendrimers were then added to the trans side of αHL pore at a distance equivalent to twice the radius of gyration of dendrimer.…”
mentioning
confidence: 99%